2003
DOI: 10.1002/jso.10275
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of preoperative serum C‐reactive protein level is related to poor prognosis in esophageal squamous cell carcinoma

Abstract: A high CRP level is associated with tumor progression and poor survival in patients with esophageal squamous cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
115
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 27 publications
9
115
0
1
Order By: Relevance
“…Therefore, the results of the present study are consistent with C-reactive protein, measured before surgery, having prognostic value independent of established pathological criteria in patients with resectable oesophageal cancer (Nozoe et al, 2001;Ikeda et al, 2003;Shimada et al, 2003). Moreover, we have shown that an elevated C-reactive protein concentration, before surgery, is associated with poor cancer-specific survival in patients undergoing potentially curative resection for gastro-oesophageal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, the results of the present study are consistent with C-reactive protein, measured before surgery, having prognostic value independent of established pathological criteria in patients with resectable oesophageal cancer (Nozoe et al, 2001;Ikeda et al, 2003;Shimada et al, 2003). Moreover, we have shown that an elevated C-reactive protein concentration, before surgery, is associated with poor cancer-specific survival in patients undergoing potentially curative resection for gastro-oesophageal adenocarcinoma.…”
Section: Discussionsupporting
confidence: 89%
“…There have been three previous studies from Japan that have shown the prognostic value of an elevated C-reactive protein concentration in patients undergoing resection for oesophageal cancer. However, in contrast with the present study, they included patients with primarily (490%) squamous tumours (Nozoe et al, 2001;Ikeda et al, 2003;Shimada et al, 2003), patients receiving neo-adjuvant treatment (Nozoe et al, 2001;Ikeda et al, 2003), patients who had advanced disease before surgery (Nozoe et al, 2001;Ikeda et al, 2003), they used a threshold for C-reactive protein of 45 mg l À1 (Nozoe et al, 2001;Ikeda et al, 2003) and the positive to total lymph node ratio was not assessed (Nozoe et al, 2001;Ikeda et al, 2003;Shimada et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of serum CRP is a common feature in patients with malignancies which has been found to be adversely prognostic, with patients having elevated CRP levels (Nozoe et al, 1998;Nakanishi et al, 2002;Shimada et al, 2003;Hashimoto et al, 2005). Growing evidence suggests prognostic importance because increased CRP levels are associated with the production of cytokines from tumour cells (Kurzrock, 1997;Legouffe et al, 1998, Yamamura et al, 1998.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the prognostic value of baseline biological markers including high levels of b2-microglobulin (B2-M), lactate dehydrogenase (LDH), and serum albumin (Bataille et al, 1992), elevations of serum C-reactive protein (CRP) have been consistently associated with a poor prognosis in myeloma (Tienhaara et al, 1994;Kaneko et al, 2002;Terpos et al, 2003). Several studies regarding the role of preoperative CRP as a predictive indicator for the malignant potential and prognosis in various other cancers have been published (Nozoe et al, 1998;Nakanishi et al, 2002;Shimada et al, 2003;Hashimoto et al, 2005). However, the prognostic significance based on preoperative CRP has not been clarified for myeloma patients, yet.…”
mentioning
confidence: 99%